2005
DOI: 10.1093/humrep/dei119
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of ICSI in HIV-1-infected women

Abstract: The results of this preliminary series of ICSI cycles in HIV-1-infected women indicate that optimal ovarian stimulation is slightly more difficult to achieve than in matched seronegative women. However, when criteria for oocyte retrieval were fulfilled, ICSI results were similar to those of age-matched controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
30
0
13

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 19 publications
2
30
0
13
Order By: Relevance
“…Likewise, acceptable pregnancy rates of 23.9% were reported in female-HIV couples (16). In an agematched controlled study, pregnancy rates in HIV-infected women were similar to controls (16.1% vs. 19.6%; not significant) (17). Prisant et al (20) recently reported unaltered pregnancy rates in HIV-infected couples.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Likewise, acceptable pregnancy rates of 23.9% were reported in female-HIV couples (16). In an agematched controlled study, pregnancy rates in HIV-infected women were similar to controls (16.1% vs. 19.6%; not significant) (17). Prisant et al (20) recently reported unaltered pregnancy rates in HIV-infected couples.…”
mentioning
confidence: 85%
“…To date, studies have reported >4,000 ART procedures in HIV men, confirming that ART effectively protects from horizontal virus transmission (10)(11)(12)(13)(14). ART experience in HIV-infected women is sparser, with <200 couples reported to date (15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 97%
“…The fact that vertical transmission from mother to fetus can be greatly reduced but not eliminated rightfully raises many ethical concerns. As seen in France, it may be appropriate to have parameters in which HIV-seropositive women are allowed to proceed with IVF, such as requiring CD4 counts of >200 per cubic millimeter, stable viral counts, and the absence of ongoing HIV disease (11). The direct-threat defense also could be applied to the potential of infecting other embryos in the laboratory, because there are reports of cross-contamination with HIV in nitrogen storage tanks (40).…”
Section: Three Different Hiv-seropositive Patient Scenariosmentioning
confidence: 99%
“…As far back as 2001, a Fertility and Sterility Modern Trends article concluded that it is neither ethically nor legally justifiable to categorically exclude individuals from infertility services on the basis of HIV infection (10). In France, HIV-seropositive women with CD4 counts of >200 per cubic millimeter, stable viral counts, and the absence of ongoing HIV disease expressly are allowed access to infertility services by French law (11). Nevertheless, in the United States, it is estimated that in 2006, <10 centers providing infertility services granted access to HIV-seropositive patients (12).…”
mentioning
confidence: 99%
“…The emergence of more effective antiretroviral treatment engendered important reductions in viral replication and significant improvement in the immune systems of patients. These advances in treatment resulted in extended life expectancy, improved quality of life, and decreased risk of sexual and vertical transmission (1% to 2%) (2)(3)(4). Advances in semen preparation (5) were followed by the use of intrauterine insemination (IUI) in HIV serodiscordant couples, which resulted in a low risk of transmission.…”
mentioning
confidence: 99%